Exosomes in the tumor microenvironment: Promoting cancer progression - Jin, Ye; Xing, Jianming; Xu, Kejin; Liu, Da; Zhuo, Yue (Frontiers in Immunology, 2022)
Exosomes, which are extracellular vesicles produced by endosomes, are important performers of intercellular communication functions. For more than three decades, there has been a growing awareness of exosomes as the contents of the tumor microenvironment and their intimate connection to the development of cancer. The composition, generation, and uptake of exosomes as well as their roles in tumor metastasis, angiogenesis, and immunosuppression are discussed in this paper. In order to stop the progression of cancer, it is crucial to find new diagnostic biomarkers and therapeutic targets for the disease. Knowing the biological characteristics of exosomes and their functions in tumor development helps in this endeavor.